Economic Policy Uncertainty and Firm Value: The Role of Company Debt - Syahrud Apriansyah; Kamaludin Kamaludin; Intan Zoraya; Mukti Trio Putra; Chairil Afandy (APMBA (Asia Pacific Management and Business Application))
This study examines the impact of economic policy uncertainty (EPU) on firm value, integrating several variables to enhance the understanding of this relationship. These variables include corporate leverage, debt restructuring, and firm performance. The data for this research were collected through a purposive sampling method, focusing on the financial statements of manufacturing companies in the ASEAN region from 2018 to 2023. The analysis will employ panel data regression techniques, utilizing the Eviews12 application. The findings indicate that EPU significantly affects corporate leverage, performance, and firm value. However, leverage, as proxied by Debt-to-Asset Ratio (DAR) and Debt-to-Capital Ratio (DCR), does not fully account for the performance and value of firms; only the DCR demonstrates a significant impact. Moreover, DCR is found to mediate the relationship between EPU and corporate performance or firm value. In contrast, debt restructuring does not moderate the effect of EPU on corporate performance. Lastly, it is evident that company performance significantly influences firm value and can mediate the impact of EPU on that value.